Neighbourhood Semantics for Graded Modal Logic - Chen, Jinsheng; van Ditmarsch, Hans; Greco, Giuseppe; Tzimoulis, Apostolos (Bulletin of the Section of Logic, 2021)
We introduce a class of neighbourhood frames for graded modal logic embedding Kripke frames into neighbourhood frames. This class of neighbourhood frames is shown to be first-order definable but not modally definable. We also obtain a new definition of graded bisimulation with respect to Kripke frames by modifying the definition of monotonic bisimulation.